PERLINDUNGAN HUKUM INVESTOR DALAM ANALISIS PEMBIAYAAN TRANSAKSI MARJIN OLEH PERUSAHAAN EFEK KETIKA DILAKUKAN PENJUALAN SAHAM SECARA PAKSA - Linda Ismaya (RECHTSTAAT, 2014)
forced sell on margin trading financing is securities selling which done forcefully with or without announcement or investor’s approval. Some cases related to this force selling considered as a violation of investor’s rights. This research purposed to knowing whether force selling on margin trading financing by securities fulfilled by the investor legal protection and how is the investor legal protection ideal concept in force selling. This research was using statute approach and conseptual approach. Based on the result of the research, force selling as written on the Bapepam-LK Rule Number V.D.6 has been appropriated by the Indonesian Civil Code but this rule against investor legal protection as ruled on The Capital Market Law and The consumer Protection Law. The investor legal protection concept consists of preventive protection and repressive protection.Key Words: Capital Market, Margin Trading Financing, Force Selling, Securities, Investor